2002
DOI: 10.1093/ps/81.7.1038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supplemental lysine, isoleucine, threonine, tryptophan and total sulfur amino acids on egg weight of Hy-line W-36 hens

Abstract: Four experiments were conducted to determine whether synthetic lysine, isoleucine, threonine, and tryptophan (LITT) or TSAA supplementation to diets formulated based on lysine improved egg weight (EW) and hen performance. In Experiment 1, diets were formulated with three TSAA levels (0.65,0.72, and 0.81%). These diets were fed with and without adding lysine and isoleucine each at 0.055% and threonine and tryptophan each at 0.022%. Treatments were randomly assigned to 960 Hy-Line W-36 hens in eight replicates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 10 publications
3
14
0
12
Order By: Relevance
“…Neste experimento, esse consumo de lisina foi obtido com o nível de 900 mg lisina digestível/kg de ração. Sohail et al (2002) verificaram que a massa de ovos não foi afetada pelos níveis de 0,65; 0,72 e 0,81% lisina total.…”
Section: Resultsunclassified
“…Neste experimento, esse consumo de lisina foi obtido com o nível de 900 mg lisina digestível/kg de ração. Sohail et al (2002) verificaram que a massa de ovos não foi afetada pelos níveis de 0,65; 0,72 e 0,81% lisina total.…”
Section: Resultsunclassified
“…Resultados semelhantes foram encontrados por Petersen (1993) e Harms & Russell (1998), que, ao avaliarem a influên-cia da metionina e da proteína na dieta de poedeiras comerciais, encontraram que o peso dos ovos aumentou conforme se aumentava o nível de metionina da dieta. Sohail et al (2002), ao estudarem os efeitos de dietas formuladas com três níveis de aminoácidos sulfurados totais e de proteína (0,81 e 18,05; 0,72 e 16,66 e 0,65 e 15,55% de aminoácidos sulfurados totais e proteína, respectivamente), em 960 poedeiras da linhagem Hy-Line com 21 semanas de idade sobre o peso dos ovos, observaram avanço linear deste parâmetro à medida que se aumentava a porcentagem de aminoácidos sulfurados totais da dieta.…”
Section: Resultsunclassified
“…Para a determinação da porcentagem de casca, as cascas foram secas em estufa de 60ºC durante três dias e depois pesadas para a realização do cálculo. Para obtenção da Unidade Haugh, determinou-se a altura do albúmen, por meio de paquímetro, e efetuou-se o cálculo, empregando-se a fórmula sugerida por Stadelman & Cotterill (1986): UH = 100 log (H + 7,57 -1,7 W 0,37 ), em que H = altura do albúmen (mm); W = peso do ovo (g); 7,57 = fator de correção para altura do albúmen; e 1,7 = fator de correção para peso do ovo.…”
Section: Methodsunclassified
“…Many authors have shown that the amount of methionine in the diet is of significant importance for production performance in laying hens. According to Sohail et al (2002) egg weight, egg production and feed consumption increased linearly as dietary total sulphur AAs increased, and Harms and Russell (1998) reported an increase in egg production, egg weight and egg mass as the level of methionine was increased. The NRC (1994) recommendation of methionine is 300 mg/hen per day.…”
Section: Discussionmentioning
confidence: 99%